Wolfram (DIDMOAD) Syndrome: A Case Report - Güngör, Serdal; Gürgöze, Metin Kaya (Fırat University, 2001)
Wolfram Syndrome is consists of the combination of diabetes insipidus, type I diabetes mellitus, optic atrophy and hearing loss. Urinary tract anomalies such as hidronefroz, megaureter and sort stature occurs with this sandrome. Here, after following the type I diabetes mellitus diagnosis for a long time, we have diagnosed two DIDMOAD cases.Because precent the delayed diagnosis, all cases with type diabetes mellitus have to examined carefully for optic atrophy and diabetes insipidus.

Wolfram sendromu diabetes insipidus, diabetes mellitus, optik atrofi ve nörosensoriyel işitme kaybı kombinasyonundan oluşur. Bu sendromda hidronefroz, megaüreter gibi üriner sistem bozuklukları ve boy kısalığı da birlikte görülebilir. Burada, tip I diabetes mellitus tanısı ile uzun zaman izlendikten sonra tanı konan iki DİDMOAD olgusu sunulmaktadır.Tanı gecikmesinin önlenmesi için tip I diabetes mellitus tanısı alan her olgu optik atrofi ve diabetes insipidus açısından özenle değerlendirilmelidir.
WOLFRAM (DİDMOAD) SENDROMU: Olgu Sunumu